2021
DOI: 10.1038/s41598-021-94962-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and genetic characteristics of Blastocystis hominis and Cystoisospora belli in HIV/AIDS patients in Guangxi Zhuang Autonomous Region, China

Abstract: Blastocystis hominis and Cystoisospora belli are considered to be common opportunistic intestinal protozoa in HIV/AIDS patients. In order to investigate the prevalence and genetic characteristics of B. hominis and C. belli in HIV/AIDS patients, a total of 285 faecal samples were individually collected from HIV/AIDS patients in Guangxi, China. B. hominis and C. belli were investigated by amplifying the barcode region of the SSU rRNA gene and the internal transcribed spacer 1 (ITS-1) region of the rRNA gene, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…In neighboring countries, optical microscopy revealed Blastocystis rates of 32.1% in Algeria, 22.1% in Libya, and 13% in Tunisia [ 1 , 2 , 44 ]. The primary mode of Blastocystis transmission is the fecal-oral route, often occurring through contact with contaminated objects, foods, and drinking water, and even with contact with infected animals [ 12 , 31 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In neighboring countries, optical microscopy revealed Blastocystis rates of 32.1% in Algeria, 22.1% in Libya, and 13% in Tunisia [ 1 , 2 , 44 ]. The primary mode of Blastocystis transmission is the fecal-oral route, often occurring through contact with contaminated objects, foods, and drinking water, and even with contact with infected animals [ 12 , 31 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several risk factors, including age, gender, personal hygiene, education level, socio-economic status, parasitosis history, and health infrastructure access, have been associated with Blastocystis infection [ 11 , 66 ]. However, our study showed no significant association between Blastocystis sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of HIV/AIDS varies widely across China 1 2. Guangxi Zhuang Autonomous Region, the only minority region in southern China, is a serious HIV/AIDS hotspot; in the past decade, this region had a much higher HIV/AIDS prevalence than any other Chinese coastal or inland province 3 4. Therefore, the public health administration in Guangxi is attempting to expand the scale of HIV screening to diagnose HIV-infected patients at an early stage and provide highly active antiretroviral therapy (HAART) promptly to reduce HIV/AIDS mortality and transmission,5 6 especially in high-risk populations 7…”
Section: Introductionmentioning
confidence: 99%